ASSESSMENT OF INHALERS TECHNIQUE PROPER USE FOR PATIENTS WITH CHRONIC RESPIRATORY DISEASES IN PRIMARY AND SECONDARY CLINICS IN BABYLON CITY - Shammer, Noor Hassan; Salih Baay, Ali (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Although the inhalers are the preferred method of medications delivery, evidences suggest that many patients are unable to use their inhalers effectively due to improper technique so patients must know the right way of their inhaler use. The aim of the study is to assess the patient's ability to use their inhalers properly, identify the most common error made, assess the benefit of single education session, compare the property of the use between the primary and secondary clinics patients, determine which type of the inhaler devices is associated with more errors, and to identify the association between the inhaler technique and the disease control. Methods: Non-randomized interventional study was done on 100 inhaler users of three inhaler types (metered-dose inhaler [p MDI], Turbuhaler, or Handihaler) for chronic respiratory diseases. Inhaler technique was evaluated by a scoring system before and after single session of training. Results: It had been shown that the current education about inhalers techniques was not sufficient. The response to single session of education was higher with high level of education, urban area, and specialized respiratory center. Better disease control with the better score. After training, the younger patients have higher score. Conclusion: We conclude that we need to stress on the most reported defect, metered-dose inhaler had the lowest mean score; therefore, it needs more training. Furthermore, single class of training can be beneficial but need follow-up to see if this effect can be maintained.